2019
DOI: 10.1111/grs.12230
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nitrogen transformation dynamics in alfalfa and red clover and their mixture silages

Abstract: The objective of this experiment was to characterize the dynamics of nitrogen (N) transformations in alfalfa and red clover and their mixture during ensiling. Alfalfa, red clover and a mixture of them (1:1 on fresh weight) were ensiled for 3, 5, 7, 14 and 30 days. The fermentation qualities and dynamic change of N components of the three silages were determined. Red clover and mixed silages showed better fermentation qualities, indicated by lower (p < 0.05) pH value, higher (p < 0.05) lactic acid concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Fermentation quality could affect the process of proteolysis of ensiled alfalfa, as proteases are sensitive to pH. Treatments which contained any of the used percentages of red clover, as well as the ones which received the higher dose of oak tannin, reduced the ammonia nitrogen (NH3-N) content, which is similar to the results obtained by Herremans et al (2019), and Dong et al (2019). This suggests that the use of oak tannin and red clover in certain proportions had a positive influence on the microbial proteolysis during the process of ensiling.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Fermentation quality could affect the process of proteolysis of ensiled alfalfa, as proteases are sensitive to pH. Treatments which contained any of the used percentages of red clover, as well as the ones which received the higher dose of oak tannin, reduced the ammonia nitrogen (NH3-N) content, which is similar to the results obtained by Herremans et al (2019), and Dong et al (2019). This suggests that the use of oak tannin and red clover in certain proportions had a positive influence on the microbial proteolysis during the process of ensiling.…”
Section: Resultssupporting
confidence: 70%
“…In alfalfa, 44 -87% of protein is degraded to non-protein nitrogen (NPN) compounds during silage fermentation, whereas for red clover of similar protein content, only 7-40% of the protein is lost due to plant proteolytic degradation (Jones et al, 1995). The high extent of protein degradation in ensiled alfalfa leads to the low utilization of forage nitrogen (N) by ruminants, thus resulting in economic losses to farmers and adverse environmental impacts (Dong et al, 2019). Inhibited proteolysis in ensiled red clover was connected by various studies with polyphenol oxidase (Mayer, 1986), a coppercontaining enzyme naturally present in red clover (Jones et al, 1995;Sullivan and Hatfield, 2006).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the formula reported by Porter et al (1995), DM loss was calculated using the corrected DM content. The pH value, ammonia-N, alcohol, lactic acid, and volatile fatty acids in ensiled alfalfa were determined according to the method reported by Dong et al (2019).…”
Section: Microbial and Chemical Analysesmentioning
confidence: 99%
“…However, in order to pursue high DM yield and starch content, WT harvest at the dough stage might face the risk of decreasing crude protein (CP) content (Xie et al, 2012;Li et al, 2016). A large number of legumes were planted as a green manure crop, which can improve production conditions of the post crops, and some legumes were also often ensiled as forage, while higher buffering capacity and lower watersoluble carbohydrate (WSC) content increased the protein degradation during ensiling (Dong et al, 2019). Some studies have shown that the appropriate ratio of WT and kura clover (Trifolium ambiguum M.…”
mentioning
confidence: 99%